CSR disclosure and state ownership: implications for earnings management and market value - Garanina, Tatiana (Emerald, 2023)
Purpose This paper explores the relationship between earnings management and firms' value through the moderating effect of the missing elements – corporate social responsibility (CSR) disclosure and state ownership in Russian companies. The main argument of the paper is that CSR disclosure can be used as a mitigating mechanism to weaken the negative relationship between earnings manipulation and market value. Additionally test whether state ownership is an important moderating factor in this relationship are conducted as state has always played an important role in the emerging Russian market. Design/methodology/approach The hypotheses are tested on panel data for 223 publicly listed Russian firms for the period 2012–2018. A number of robustness tests are used to check the obtained results for consistency. Following previous research GMM method is employed to address endogeneity concerns. Findings Supported by stakeholder theory, it is observed that firms that disclosed more CSR information experience a weaker negative relationship between earnings management and market value because investors and other stakeholders positively evaluate a positive CSR image. This negative effect of earnings management on market value is even weaker for state-owned companies as market participants appreciate involvement of state-owned companies in CSR activities and place greater expectations on these firms to be responsible without clear understanding whether these actions are “window dressing” for this type of companies or not. Originality/value The study results provide new insights into the relation between earnings management, firm's value, CSR disclosure and state ownership in emerging-market firms. The paper highlight the importance of considering country-specific factors, such as state ownership, while analysing the market reaction on CSR disclosure and earnings management since the institutional peculiarities may help to explain differences in the obtained results.
Keywords: CSR disclosure; Earnings management; State ownership; Tobin’s Q; Emerging markets; Russia; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|